A new taxon of Hypericum (Hypericaceae) from southeastern Turkey - Özgi̇şi̇, Kurtuluş; Ocak, Ati̇la (Phytotaxa, 2021)
Hypericum malatyanum subsp. nurhakense is described as a new taxon from Kahramanmaraş, Turkey. Morphologically, it is similar to Hypericum malatyanum subsp. malatyanum, but is easily distinguished by several morphological characters, including the shape of its bracts and bracteoles, the shape of sepals, the gland type on the sepal margin, the number of cilia on the petal margin, and features of seeds. Diagnostic characters, a detailed description, and photographs of the new taxon are given; the IUCN Red List category and observations on the ecology of the populations are noted; and the distribution map of the new taxon and its closely related relatives in Turkey are presented.